Chitchat: Celebrating the World's Languages - Jude Isabella (Ontario, Canada Kids Can Press, 2013)
Award-winning children's science writer Jude Isabella has compiled everything a young reader would ever want to know about language into one accessible, visually stunning book. In lively text, both spoken and written language are explored, including: a basic history of human's use of language; how individuals learn language as babies, and why; how writing systems and alphabets differ; the many sources and uses of slang through the years; how languages evolved in different parts of the world; and why some languages became extinct. Throughout the pages, more than fifty world languages are highlighted and children are offered opportunities to try out some phrases. Each separate topic is covered on a two-page spread, making the content manageable and approachable, and each spread is enhanced wi..
Keywords: Circle Time; Global Cultures / Traditions -- Global Cultures / Traditions